2001
DOI: 10.1109/42.932744
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of pulmonary nodules in helical CT images based on an improved template-matching technique

Abstract: The purpose of this study is to develop a technique for computer-aided diagnosis (CAD) systems to detect lung nodules in helical X-ray pulmonary computed tomography CT) images. We propose a novel template-matching technique based on a genetic algorithm (GA) template matching (GATM) for detecting nodules existing within the lung area; the GA was used to determine the target position in the observed image efficiently and to select an adequate template image from several reference patterns for quick template matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(57 citation statements)
references
References 12 publications
2
52
0
Order By: Relevance
“…A template matching technique which is based on genetic algorithm was proposed in Lee et al (2001) for detecting lung nodules in chest CT scans. This method was validated on 20 clinical cases of a private dataset and a rule-based classifier was used to reduce the number of false positives (Fps).…”
Section: Introductionmentioning
confidence: 99%
“…A template matching technique which is based on genetic algorithm was proposed in Lee et al (2001) for detecting lung nodules in chest CT scans. This method was validated on 20 clinical cases of a private dataset and a rule-based classifier was used to reduce the number of false positives (Fps).…”
Section: Introductionmentioning
confidence: 99%
“…A number of research groups have reported a variety of CAD systems for detecting lung nodules in chest CT images, including multiple grayscale thresholding [5,6] , local density maximum algorithm [7] , fuzzy clustering [8] , genetic algorithm template matching of Gaussian spheres and discs [9] , filters enhancing spherical structures [10][11][12][13] , curved surface morphology analysis [14] , and volumetric curvature-based thresholding and region growing [15] . Commercial CAD systems for detecting lung nodules in chest CT images have also been developed, including the ImageChecker CT Lung system (R2 Technology Inc., Sunnyvale, CA, USA), Lung VCAR (GE Healthcare Technologies, Waukesha, WI, USA), and Syngo Lung CAD (Siemens Medical Solutions, Erlangen, Germany).…”
Section: Introductionmentioning
confidence: 99%
“…Kim, et al, 2003) (Brown MS, et al, 2003) (Lee Y, et al, 2001), however, is more difficult than that of isolated or juxtapleural nodules because vascular nodules are attached to the pulmonary vessels. Vascular nodules are distinguished morphologically from the vessels because they are typically spherical in shape, while the vessels are elongated.…”
Section: Vascular Nodule Candidatesmentioning
confidence: 99%
“…A number of methods and systems for automated nodule detection are developed over the years (D.-Y. Kim, et al, 2003) (Brown MS, et al, 2003) (Lee Y, et al, 2001), some are focused on the "density" (considering the fact that lung nodules have relatively higher densities than those of lung parenchyma) while others are focused on "model" (considering some features like compactness, elongation and size).…”
Section: Previous Workmentioning
confidence: 99%